Effect of tumor necrosis factor-α inhibitors on ambulatory 24-h blood pressure. (2nd January 2017) - Grossman, Chagai; Bornstein, Gil; Leibowitz, Avshalom; Ben-Zvi, Ilan; Grossman, Ehud
Abstract: Tumor necrosis factor alpha (TNF-α) inhibitors are increasingly being used in inflammatory rheumatic diseases (IRD). The risk of cardiovascular disease is elevated in patients with IRD and TNF-α inhibitors reduce this risk. We assessed whether the beneficial effect of TNF-α inhibitors on cardiovascular risk is mediated by blood pressure reduction. We measured blood pressure levels with 24-h ambulatory blood pressure measurements device in patients with IRD before and 3 months after treatment with TNF-α inhibitors. The study population consisted of 15 subjects (6 men; mean age 45.9 ± 14.1 years). Most patients had either rheumatoid arthritis or psoriatic arthritis and adalimumab was the most common TNF-α inhibitor used. Mean 24-h systolic and diastolic blood pressure levels remained the same after treatment (121 ± 12/66 ± 7 before and 123 ± 11/67 ± 10 mm Hg after; p = 0.88 and 0.66, respectively). The study demonstrates that TNF-α inhibitors have no effect on blood pressure levels.